PELAKSANAAN EVALUASI PEMBELAJARAN IPS BERBASIS KTSP KELAS V (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
The purpose of this study is to describe the evaluation of learning social studies contained in the class V SD Negeri Semarang District of Gunungpati at KD 2.4 ie appreciate the struggles of the characters in maintaining independence. This research was conducted in six primary schools Gunungpati District of Semarang. This study used qualitative research methods. Data collection techniques used were observation, interviews, documentation, field notes, as well as triangulation. The results showed that 1) Overall was a teacher in the fifth grade elementary school as research areas have been carrying out evaluation of learning according to the mandate set out in Permenfiknas No. 16, 2007 .. (2) Master Class V in primary schools where research was conducted to evaluate the results of social studies students through the activities of daily tests, homework, and administration tasks. Based on the results of research and discussion, the researchers advise sevagai the following (1) The evaluation study conducted by the Social Science teacher Class V is expected to be as objective as possible by making the assessment format in accordance with the basic competencies evaluated .. (2) The evaluation of learning IPS done by teachers Class V is not expected to stop at the stage of entering values only, but will also use the results of the evaluation as a means to improve the quality of learning.